Genetic sequence stratigraphy on the basis of ichnology for the Middle Jurassic basin margin succession of Chorar Island (eastern Kachchh Basin, western India) - Darngawn, Jehova L.; Patel, Satish J.; Joseph, Jaquilin K.; Shitole, Apuva D. (Geologos, 2019)
Synrift basin margin successions are greatly influenced by eustatic sea level changes, tectonics and accommodation space filled in by sediments. The Middle Jurassic (Bajocian–Callovian) of Chorar Island (western India) comprises a ~109-m-thick synrift basin margin succession of clastic, non-clastic and mixed siliciclastic-carbonate rocks which are here analysed and categorised into nine lithofacies. The succession is bioturbated to varying intensities; 16 identified ichnogenera can be assigned to environmentally related groups of five trace fossil assemblages, which include Gyrochorte, Hillichnus, Rhizocorallium, Skolithos and Thalassinoides. These ichnoassemblages document the Skolithos and Cruziana Ichnofacies which marks a change in energy conditions, sedimentation dispersal patterns and bathymetry in a shallow-marine environment. The Bajocian–Callovian succession is further analysed on the basis of sedimentological and ichnological data that show two genetic sequences consisting of Transgressive Systems Tract and Highstand Systems Tract bounded by Maximum Flooding Surface. The synrift basin margin succession of the Middle Jurassic of Chorar Island shows cyclicity in deposition; the Bajocian–Bathonian succession represents progradational to retrogradational coastlines, while the Callovian succession documents an aggrading progradational coastline.